2000
DOI: 10.1038/sj.bjp.0703488
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cholinergic airway reactivity and nitric oxide production by endogenous arginase activity

Abstract: 1 Cholinergic airway constriction is functionally antagonized by agonist-induced constitutive nitric oxide synthase (cNOS)-derived nitric oxide (NO). Since cNOS and arginase, which hydrolyzes Larginine to L-ornithine and urea, use L-arginine as a common substrate, competition between both enzymes for the substrate could be involved in the regulation of cholinergic airway reactivity. Using a perfused guinea-pig tracheal tube preparation, we investigated the modulation of methacholineinduced airway constriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 43 publications
4
66
0
6
Order By: Relevance
“…Endotoxin (lipopolysaccharide) administration in macrophages resulted in the coinduction of the Arg isoforms Arg I and Arg II, and inducible NOS (iNOS), leading to the hypothesis that Arg may limit sustained overproduction of NO by limiting substrate availability to iNOS (12,26,41,42). Recently, Arg I and Arg II expression have been demonstrated in the rat lung, where they modulate cholinergic airway responses and NO activity (43). Arg I and Arg II expression has also been demonstrated in the penis (11,16) and A293 cells overexpressing NOS1 (44), where reciprocal regulation of Arg and constitutive NOS1 exists.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin (lipopolysaccharide) administration in macrophages resulted in the coinduction of the Arg isoforms Arg I and Arg II, and inducible NOS (iNOS), leading to the hypothesis that Arg may limit sustained overproduction of NO by limiting substrate availability to iNOS (12,26,41,42). Recently, Arg I and Arg II expression have been demonstrated in the rat lung, where they modulate cholinergic airway responses and NO activity (43). Arg I and Arg II expression has also been demonstrated in the penis (11,16) and A293 cells overexpressing NOS1 (44), where reciprocal regulation of Arg and constitutive NOS1 exists.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 In the airway, arginase inhibition attenuates methacholine-induced airway constriction by increasing NO production. 28 Arginase may also limit NO production in macrophages and other tissue after NOS2 induction. 6,29,30 Furthermore, arginase may limit NOS activity in A293 cells overexpressing NOS1 31 and regulate vascular smooth muscle proliferation in an NO-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Arginase I and II are both expressed constitutively in the airways, particularly in epithelial cells, (myo)fibroblasts and alveolar macrophages [113][114][115]. In guinea pigs, it has been discovered that arginase activity is functionally involved in basal airway responsiveness by limiting cNOS-derived NO production [116]. Using airway preparations from the same animal model, it was demonstrated that increased arginase activity may be involved in allergen-induced AHR and reduced iNANC relaxation after the early asthmatic reaction [96,111].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 99%